Enhanching Expository Text Writing Ability Through Project-Based Learning for Broadcasting Students - Sanita Fitri; Rini Fadhillah Putri (STKIP Taman Siswa Bima, 2025)
This study aims to develop expository text writing skills of Grade 10 students majoring in Broadcasting at SMK Swasta Dwi Tunggal through the implementation of the Project-Based Learning (PjBL) model. The problems identified include low student motivation, poor logical structure in writing, and the continued use of teacher-centered learning models. The method applied was Research and Development (R&D) based on Borg and Gall's model. Data were collected through interviews, writing tests (pre-test and post-test), and analysis of student writing samples. The findings revealed that implementing PjBL significantly improved students' writing abilities, with the average score increasing from 65.1 (pre-test) to 86.3 (post-test). The N-Gain scores were categorized as medium to high. Students also demonstrated improvement in content development, text organization, language use, and writing mechanics. These findings suggest that the PjBL model is effective in enhancing students' expository writing skills in vocational contexts, particularly in the Broadcasting field.